Postdoctoral Research and Informal Mentoring: A Reflective Inquiry - Sandi M. Van Lieu; Manyu Li (Journal of Scholarly Engagement)
This article reflects on an informal mentoring project that took place between an established faculty member with grant-writing and research experience and another faculty member who was finishing her doctoral degree and had no experience in applying for grants or submitting to peer-reviewed publications. After the project, the doctoral student reflected on her experience using Graham Gibbs’ reflective model and discovered why this mentor/mentee relationship was effective despite the fact that all communication took place via email. The results were the authors concluding how important mentorships are for doctoral students.